PRIMARY SCHOOL TEACHERS' PERCEPTION OF THE 2025 FREE NUTRITIONAL MEAL PROGRAM IN BERASTAGI DISTRICT, KARO REGENCY - Fitriani, Rahma; Barus, Julius Boy Nesra Basgimata; Gule, Yosefo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Free Nutritious Meal Program is a government policy aimed at improving students' nutritional needs, health, and learning readiness. However, implementing this program still requires support from schools, especially teachers, as they play a direct role in assisting students in the school environment. This study aims to determine elementary school teachers' perceptions of the 2025 Free Nutritious Meal Program at SD Swasta Masehi Berastagi. This study used a descriptive, quantitative approach with a purposive sample of 25 teachers. Data were collected through a closed-ended Likert-scale questionnaire and documentation, then analyzed using descriptive statistics, including frequencies, percentages, and score categories. The results showed that teachers' perceptions were in the very positive category. In the cognitive aspect, the majority of teachers understood the program's goals and benefits, with 68.10% agreeing and 14.29% strongly agreeing. In the affective aspect, teachers showed an attitude of acceptance and support for the program, with 68.78% agreeing and 20.11% strongly agreeing. Regarding psychomotor aspects, teachers were ready to act, with 71.98% agreeing and 17.67% strongly agreeing. In conclusion, the Free Nutritious Meal Program was well-received by teachers and has the potential to be implemented in schools. However, further outreach, technical strengthening, and supporting facilities are still needed.